Working Class America: Essays on Labor, Community, and American Society - Barrett, James R. (Labour / Le Travail, 1985)
This article reviews the book "Working Class America: Essays on Labor, Community, and American Society," by Michael H. Frisch. & Daniel J. Walkowitz, edited.
Keywords: Essays; FRISCH; Michael H.; Nonfiction; REVIEWS; WALKOWITZ; Daniel J.; WORKING Class America: Essays on Labor; Community & American Society (Book); books